Nitrogen Regulates the Distribution of Antibiotic Resistance Genes in the Soil–Vegetable System - Wang, Tingting; Sun, Silu; Xu, Yanxing; Waigi, Michael Gatheru; Odinga, Emmanuel Stephen; Vasilyeva, Galina K.; Gao, Yanzheng; Hu, Xiaojie (Frontiers in Microbiology, 2022)
The increasing antibiotic resistance genes (ARGs) in fertilizer-amended soils can potentially enter food chains through their transfer in a soil-vegetable system, thus, posing threats to human health. As nitrogen is an essential nutrient in agricultural production, the effect of nitrogen (in the forms NH4+-N and NO3–-N) on ARG (blaTEM-1, sul1, tnpA-4, cmlA, str, and tetO) distribution in a soil-Chinese cabbage system was investigated. Not all ARGs could transfer from soil to vegetable. For transferable ones (blaTEM-1, sul1, and tnpA-4), nitrogen application influenced their abundances in soil and vegetable but did not impact their distribution patterns (i.e., preference to either leaf or root tissues). For ARG abundances in soil, nitrogen effects varied over time, and effect of NH4+-N was more significant than that of NO3–-N. The ARG accumulation to vegetables was affected by nitrogen application, and the nitrogen form was no longer a key influencing factor. In most cases, ARGs were found to prefer being enriched in roots, and nitrogen application may slightly affect their migration from root to leaf. The calculated estimated human intake values indicated that both children and adults could intake 106–107 copies of ARGs per day from cabbage consumption, and nitrogen application affected ARG intake to varying degrees. These results provided a new understanding of ARG distribution in vegetables under the agronomic measures such as nitrogen application, which may offer knowledge for healthy vegetable cultivation in future.